Chapter Castelli e campagne in area trentina. I rapporti tra i signori e le comunità rurali - Franceschini, Italo (Reti Medievali E-Book, 2023)
In a territory without large urban centres, such as the Trentino area, the relationship between lords and rural communities is crucial for the exploitation of resources, the administration of justice, the social control of unfree peasants.